Tracing Moyo’s Intellectual Footprint on Land and Agrarian Questions in the Global South - Zvenyika Eckson Mugari (Palgrave Macmillan, Cham, 2022)
The land question has become more topical than ever before in the Southern African region. Zimbabwe provided the test case when, beginning 2000, majority landless Africans started a land revolution from below, which forced the government to ram through legislation to enable compulsory land acquisition without compensation. On 14 November 2018, the South African Parliament passed a land bill to amend section 25 of that country’s constitution to enable the government to expropriate land without compensation for resettlement purposes. The Namibian government too is seized with working out modalities to enable it to expeditiously redress historical land ownership imbalances. This chapter is a reflection on the relevance of Sam Moyo’s critical insights on the political economy of land and labor in the Global South. Although much of his academic work is grounded on the Zimbabwean postcolonial experience with land reform, it only does so in order to bring out the microcosmic nature of the case from which valuable lessons can be drawn for wider application in resolving similar land and agrarian questions in postcolonial contexts elsewhere.